Design and Implementation of a Loan Information System at the North Lampung BKKBN Office - Anggun Rahmawati; Hartono Hartono (G-Tech: Jurnal Teknologi Terapan, 2025)
This study addresses the lack of automation in government loan management systems, which has led to inefficiencies such as delayed service, data entry errors, and difficulties in tracking borrowed items. To overcome these challenges, this research aims to design and implement a web-based goods borrowing information system for the BKKBN Office of North Lampung. The system was developed using the Waterfall methodology and adopts the Model-View-Controller (MVC) architectural pattern. It includes key features such as inventory management, user authentication, borrowing request submission, administrative verification, transaction reporting, and real-time status notifications. System evaluation through Black Box and User Acceptance Testing demonstrated that all features operated effectively and reliably, handling 234 inventory records across eight active users. The results indicate that the proposed system enhances administrative efficiency, transparency, and data accuracy, making it suitable for practical implementation and future development with features such as email notifications or QR-code integration.